Strategi Komunikasi Da’i dalam Mencegah Penyalahgunaan Narkoba di Desa Bagan dalam Kecamatan Tanjung Tiram Kabupaten Batubara - Hasibuan, Fitrah Al Khairi; Ritonga, Muhammad Husni; Nurhanifah, Nurhanifah (Lembaga Yasin AlSys, 2023)
This research aims to find out the forms of corruption in Bagan village in Tanjung Tiram sub-district, Batubara district, the communication strategy carried out by the preacher in preventing corruption in Bagan village in Tanjung Tiram sub-district, Batubara district and to find out the obstacles faced by the preachers and the solutions made by the preachers in preventing them. abuse in Bagan village in Tanjung Tiram sub-district, Coal Regency. This type of research is field research. In this study, I used a qualitative descriptive method, namely by looking for actual and detailed data and information in a non-statistical way. In data collection techniques, researchers used observation, interviews and documentation. The results of this study indicate that the form of propaganda in Bagan Village is influenced by several factors that contribute to its increase. First, the low level of education and knowledge about the dangers of drugs among the public is one of the main causes. Dai's communication in Drug Abuse in Bagan Village uses platforms such as WhatsApp and Instagram groups, Dai can reach a wider and more diverse audience. One of the main challenges we face is the misunderstanding of some people about the urgency and negative impact of drug propaganda. Some still feel that this is a problem that is far from their everyday lives and lack understanding of the potential dangers of drugs. The main obstacle that we discuss is the misunderstanding of some people regarding the urgency and negative impact of drug propaganda. Some still feel that this is a problem that is far from their everyday lives and lack understanding of the potential dangers of drugs.